University of Nairobi Students Performance in the Context of Locus of Control (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
By locus of control in Social Psychology is meant the source of control in one’s given in every person’spattern of behaviour falling into external and internal With external control locus, a person who attributesthe control locus of behaviour, as originating from outside self. In other words, one’s failure or success iscontrolled by outside forces and therefore, there is not much that can be done to exercise control of suchbehaviour. In contrast, a person who has internal locus of control holds the view that she or he isresponsible for his/her behaviour, as it does not occur on the basis of luck or chance. . In short, this servedas the motivation for wishing to determine the University of Nairobi students’ locus of control amongboth genders, male and female students.The sample size comprised 127 females and 97 males, giving atotal of 224 university students. Their age ranged from 20 to 55 years. The participants were all takingpsychology as a major subject.A questionnaire comprising 25 pairs of statements was used. Eachstatement had two options for participants to respond to as normally provided for in the Rotter’s Locus ofControl Scale.Based on Rotter’s Locus of Control Scale, there emerged both external and internal locus ofcontrol participants in uneven proportions. A chi-square statistical analysis was employed. Calculationof: x2 test [2df, N224] = 107.6,